2015
DOI: 10.3390/nu7053427
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Vitamin D Deficiency in Pregnant Korean Women: The First Trimester and the Winter Season as Risk Factors for Vitamin D Deficiency

Abstract: We investigated the vitamin D status of Korean women during pregnancy and assessed the effects of vitamin D deficiency on two pregnancy outcomes; preterm births and the births of small for gestational age. We measured the serum 25-hydroxyvitamin D levels in 220 pregnant Korean women who were recruited prospectively and compared these levels with those of 500 healthy non-pregnant women. We analyzed vitamin D status according to patient demographics, season, and obstetrical characteristics; moreover, we also ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 34 publications
7
62
2
5
Order By: Relevance
“…The score for one article, however, was unable to be evaluated because the full text was not available, and three RCT had low risk of bias. Table 1 lists the characteristics of the 18 observational studies 9,[12][13][14][15][16][17][18][19][20][21][22][23][24][30][31][32] and six RCT. [33][34][35][36][37][38] There was some disparity in the definition of PTB between studies.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…The score for one article, however, was unable to be evaluated because the full text was not available, and three RCT had low risk of bias. Table 1 lists the characteristics of the 18 observational studies 9,[12][13][14][15][16][17][18][19][20][21][22][23][24][30][31][32] and six RCT. [33][34][35][36][37][38] There was some disparity in the definition of PTB between studies.…”
Section: Literature Searchmentioning
confidence: 99%
“…8 In a survey of Asian subjects, 77.3% had circulating 25-OHD concentration < 50 nmol/L, and 28.6% had concentration <25 nmol/L. 9 Lower maternal vitamin D status during pregnancy is a risk factor for various adverse birth outcomes including PTB. 10 Epidemiologic studies and randomized trials concerning the association of maternal hypovitaminosis D during pregnancy and PTB yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The results from previous studies indicated that the vitamin D levels in Korean preterm infants were lower than those in infants in Northern European countries. 3,4 Vitamin D deficiency remains a common micronutrient disorder despite of encouragement to vitamin D supplements.…”
Section: Introductionmentioning
confidence: 99%
“…1 The high prevalence of vitamin D insufficiency during pregnancy is increasingly recognized, especially in dark women, following customs like veil, in women living in northern latitudes and during winter season. 1,3,4 Maternal effects of hypovitaminosis D have been reported to cause calcium malabsorption, bone loss, poor weight gain, subclinical myopathy, 5 increased preeclampsia (PE), 6 increased gestational diabetes mellitus (GDM), 7 increased cesarean sections. 8 In the newborn, hypovitaminosis D has been reported to cause neonatal tetany, 9 hyperbilirubinemia, 10 large fontanelle, enamel defects, congenital rickets, and infantile rickets.…”
Section: Introductionmentioning
confidence: 99%